Synthesis of Co/CNTs via strong electrostatic adsorption: Effect of metal loading - Akbarzadeh, O. (Trans Tech Publications Ltd, 2014)
Cobalt particles were deposited on treated CNTs via the Strong Electrostatic Adsorption (SEA) method. Cobalt loading on CNTs support was varied from 5 to 20 wt. Samples were characterized by N2 adsorption and HRTEM. The results of TEM indicated that increasing the metal loading from 5 to 20 resulted in larger nanoparticles and also led to agglomeration. Â© (2014) Trans Tech Publications, Switzerland.